Students’ Responses to QuizWhizzer Educational Game to Strengthen Mathematical Concept Understanding Ability - Nuthfah Faijah; Nuryadi Nuryadi; Nafida Hetty Marhaeni (Journal of Education and Teaching Learning, 2022)
Understanding concepts is an important part of mathematics. However, students' ability to understand mathematical concepts is still relatively low. For this reason, learning media are needed that can strengthen these abilities, such as the educational game QuizWhizzer. QuizWhizzer is a learning media in the form of an interesting, interactive game, prioritizing cooperation and communication, and can create positive interactions between students through games in the learning process. Therefore, the purpose of this study was to determine students' responses to the learning media in the form of the educational game QuizWhizzer to mathematical concept understanding ability. This study is a descriptive study about the level of student satisfaction in learning using the educational game QuizWhizzer. The instruments used were educational games and student response questionnaires. The population in this study were students of class VIII SMP Negeri 8 Yogyakarta, while the samples were students of class VIII-H and VIII-I. This study concludes that the use of the QuizWhizzer which contains indicators of the ability to understand concepts in the small-scale trial class and large-scale trial class obtains a positive response from students. This result is evidenced by the average score in the small-scale class is 55, while in the large-scale class it is 57. The score is in the Good classification. For this reason, the use of the QuizWhizzer educational game is stated to be practical to use for learning. The results of this study need to be developed on a larger scale considering the different characteristics of students.